A Comparative Study of 1x1, 2x1 and 2x2 MIMO-OFDM Systems Based on IEEE802.16a - Drieberg , Micheal (2004)
A comparison of 1x1, 2x1 and 2x2 multi-input multi-output (MIMO) – orthogonal frequency division multiplexing (OFDM) system based on IEEE802.16a, wireless Metropolitan Area Network (MAN) have been carried out by simulation of the systems in Matlab/Simulink. MIMO that refers to the use of multiple antennas at the transmitter and multiple antennas at the receiver is especially powerful in providing diversity to overcome the performance degradation due to channel fades. The model uses the OFDM physical (PHY) layer using QPSK constellations with Reed-Solomon and Convolutional Coding (RS-CC) scheme for forward error correction (FEC) at rate ¾. The model has been tested using all 6 Stanford University Interim (SUI) channels. The Space Time (ST) code used is Alamouti’s ST Block Code which gives very good performance and is quite simple to implement. Simulation results show that the diversity gain at BER of 10-3 when using 2x1 MISO compared to 1x1 SISO is around 10dB for all SUI channels. At the same target BER, the extra diversity gain when using 2x2 MIMO compared to 2x1 MISO range from 3 to 7dB. Also, the extra SNR required for BER at 10-6 for all 6 SUI channels are only 5-7dB more than AWGN when using 2x2 MIMO.